Pengaruh Penggunaan Gadget Terhadap Anak Usia Dini - Widiasanti, Irika; Khairunnisa, Rafifah; Agustin, Nadiya Putri; Zahrani, Maulidina; Putri, Aulia; Wibowo, Farah Qonita Dzakiyyah (Universitas Pahlawan Tuanku Tambusai, 2025)
The use of gadgets in early childhood is increasing along with the development of technology. This study aims to analyze the effect of gadget use on early childhood cognitive, social and emotional development. Through the literature method, this study analyzes various sources related to the use of gadgets in early childhood and how it affects their development. The results show that screen time of more than one hour per day can negatively affect children's social and cognitive development. Children who use gadgets more often tend to experience delays in social interaction and have lower concentration levels. However, gadgets also have educational benefits if used wisely and with parental supervision. Therefore, digital literacy emerges as a solution to reduce the negative impact of gadget use by assisting parents and educators in managing gadget use time, selecting appropriate content, and improving children's social skills.